Adrenal insufficiency in the elderly: a nationwide study of hospitalizations in Taiwan - Chen, Yi-chun; Chen, Yu-Chun; Chou, Li-Fang; Chen, Tzeng-Ji; Hwang, Shinn-Jang (The Tohoku journal of experimental medicine, 2010)
Adrenal insufficiency (AI), a life-threatening disorder, usually starts with variable nonspecific symptoms and signs of poor appetite, fatigue, fever, and gastrointestinal discomfort, and may progress to adrenal crisis with complications of electrolyte imbalance, change of consciousness or even shock. Epidemiological data about AI in the elderly population are limited. Based on nationwide hospitalization datasets in Taiwan, we retrospectively analyzed the annual incidence of AI among the elderly population (> or = 60 years old), as well as co-morbidities. The prevalence of AI increased from 6.5/10(5) (n = 1,293) in 1996 to 20.8/10(5) (n = 4,681) in 2007. In 2006, AI was newly diagnosed in 3,494 patients (1,701 women and 1,793 men), which represented an incidence of 15.5/10(5) in the whole population. Nearly four fifths (1,349 women and 1,429 men) of the patients were 60 years old and over, corresponding to an incidence of 92.4/10(5) in the elderly population. The most common co-morbidities were pneumonia (8.6%, n = 238) and urinary tract infections (6.9%, n = 193). Within the one-year observation after discharge, pneumonia was also the most frequent diagnosis in subsequent hospitalizations; besides, 178 (6.5%) patients died in the hospital and the common causes of death were respiratory failure (n = 34), septicemia (n = 23), pneumonia (n = 16), and chronic obstructive pulmonary disease (n = 9). In conclusion, the majority of the elderly have co-morbidities when AI was initially diagnosed. Infectious and pulmonary diseases as the most common co-morbidities also play a major role in subsequent hospitalizations and in-hospital deaths.